Atomic Disorders Induced by Silver and Magnesium Ion Migrations Favor High Thermoelectric Performance in α‐MgAgSb‐Based Materials. (28th September 2015) - Li, Dandan; Zhao, Huaizhou; Li, Shanming; Wei, Beipei; Shuai, Jing; Shi, Chenglong; Xi, Xuekui; Sun, Peijie; Meng, Sheng; Gu, Lin; Ren, Zhifeng; Chen, Xiaolong
Abstract : Thermoelectric devices can directly convert thermal energy to electricity or vice versa with the efficiency being determined by the materials' dimensionless figure of merit ( ZT ). Since the revival of interests in the last decades, substantial achievements have been reached in search of high‐performance thermoelectric materials, especially in the high temperature regime. In the near‐room‐temperature regime, MgAgSb‐based materials are recently obtained with ZT ≈ 0.9 at 300 K and ≈1.4 at 525 K, as well as a record high energy conversion efficiency of 8.5%. However, the underlying mechanism responsible for the performance in this family of materials has been poorly understood. Here, based on structure refinements, scanning transmission electron microscopy (STEM), NMR experiments, and density function theory (DFT) calculations, unique silver and magnesium ion migrations in α‐MgAg0.97 Sb0.99 are disclosed. It is revealed that the local atomic disorders induced by concurrent ion migrations are the major origin of the low thermal conductivity and play an important role in the good ZT in MgAgSb‐based materials. Abstract : The underlying mechanism responsible for the high thermoelectric performance in α‐MgAgSb‐based materials is disclosed. Based on density function theory calculations and experimental characterizations, concurrent silver and magnesium ion migrations are revealed in α‐MgAgSb. This is believed to be the origin of the low thermal conductivity in α‐MgAgSb‐based materials and plays an important role in the good figure of merit of these materials.